The bookshop of hidden dreams - Hawkins, Karen (Dove Pond Series, 2024)
"A magical entry in the Dove Pond series that follows a gifted historian investigating the mystery of a love story lost to time. When an antique tin of love letters is found, historian Tay Dove returns to her hometown to investigate. Reeling from a romantic betrayal, Tay hopes to distract herself by writing a biography about her famous great-grat-grandmother Sarafina Dove, who became a star reporter in the late 1890s. Tay believes the letters could be the key to understanding why Sarafina left Dove Pond so abruptly, but the missives only add to Tay's questions--especially when they reveal a forbidden love affair with William Day, a notorious train robber. Some answers might be found in eighty-two-year-old Rose Day's bookshop and town archive, but Rose is curiously reluctant to give Tay access. Just when Tay thinks she's reached a dead end, she finds an unlikely ally in Rose's grandson, Luke, a fellow puzzle lover. Together they set out to uncover what happened. . . and find a love story that could be more precious than gold."--